Daily field checking list by Walter Rosene, April 22, 1934 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 22, 1934. This checklist was used by Walter Rosene to record birds sighted around North Bridge with Bob Walker between 7:00 and 9:00 and Little Wall Lake between 4:00 and 6:00. Plustek--flatbed